Impact of starch granule-associated surface and channel proteins on physicochemical properties of corn and rice starches. (15th December 2020) - Bae, Ji-Eun; Hong, Jung Sun; Baik, Moo-Yeol; Choi, Hee-Don; Choi, Hyun-Wook; Kim, Hyun-Seok
Graphical abstract: Highlights: Protease treatment on starch at 4 °C successfully attenuate amylase activity. Protease mainly removed starch granule-associated surface/channel proteins (SGAPs). The reduction of SGAP increased starch solubility and decreased swelling power. The setback of corn and rice starch pastes were reduced by SGAPs removal. SGAPs reinforced the starch granule rigidity, increasing starch pasting viscosity. Abstract: The objective of this study was to investigate the impact of removing starch granule-associated proteins (SGAPs), especially starch granule-associated surface and channel proteins, on the overall characteristics of corn and rice starches. Protease treatment predominantly removed SGAPs on surfaces and in channels of the starches without significant damage, as evidenced by confocal laser scanning microscopy coupled with protein-specific and non-reactive fluorescent dye staining. Compared to untreated starches, protease-treated (PT) starches showed higher solubility and lower swelling power. However, there were no changes in their gelatinization and melting temperatures, despite their higher relative crystallinity. The stability of swollen starch granules during shearing was reduced following SGAP removal, reducing their peak, final and setback viscosities of the paste. Taken together these results indicate that SGAP removal predominantly affects the rheological properties of starch. Furthermore, the lower setback in PT-starch pastes suggests short-term retrogradation may be retarded by protease treatment of starch.